Implementing 1 → M Economical Phase-Covariant Telecloning in Cavity QED - Xue, Li (丽薛); Jiang, Nian-Quan (年权 姜) (Communications in theoretical physics, 2011)
We propose an experimentally feasible scheme to implement the economical 1 → M phase-covariant telecloning based on cavity QED. By the resonant interaction of the atoms with cavity field of a high-Q cavity and the different coupling strength between atoms and cavity field, the scheme can generate quantum entanglement channel in one step. What is more, the operation time and steps do not increase with the increase of atoms.